The effect of differentiated learning assisted by liveworksheet on student learning achievement in mathematics subjects in senior high school - Dahlia, Dini; Nindiasari, Hepsi (Universitas Sultan Ageng Tirtayasa, 2024)
Every year, students' academic achievements, particularly in the subject of mathematics, tend to be low. In the learning process, teachers are confronted with a diversity of potentials among learners. Therefore, teachers must possess the ability to develop learners according to their existing potentials so that their learning achievements can improve. A strategy used by educators to address every student's learning requirement is differentiated education with the help of liveworksheet. This study aims to determine if customised instruction with real-time worksheet support affects students' learning outcomes. A one-group pretest-posttest quantitative quasi-experimental design is the study methodology used. The subjects consisted of 35 students from class XII IPA-5 at SMA Negeri 1 Jawilan, Kabupaten Serang. A test was used to obtain data. The pre-test scores resulted in an average of 28,29, while the post-test scores yielded an average of 58,86. As a result, the average score increased by 30,571 between the pre- and post-tests. The paired sample t-test indicates that the rejection of H0 and acceptance of H1 is indicated by the sig value (2-tailed) of 0,000 < 0,05, based on data analysis using SPSS version 23. The results of the study demonstrate that tailored teaching based on live worksheets has an effect on the mathematical learning outcomes of students at SMA Negeri 1 Jawilan, Kabupaten Serang.